Validation of a Google Sites-Based LMS Evaluation Instrument with the Importance Performance Analysis Approach in Sustainable Learning - Sopan Hidayat; Rizka Donny Agung Saputra (Jurnal Penelitian Pendidikan IPA, 2025)
Evaluating the feasibility and performance of a Learning Management System (LMS) requires a valid and reliable assessment instrument, especially for platforms such as Google Sites that are widely used in low-resource educational settings. This study aims to validate an LMS evaluation instrument that integrates Importance Performance Analysis (IPA) and Education for Sustainable Development (ESD) indicators. A quantitative descriptive design was employed involving 40 respondents consisting of teachers and students at SMPN 1 Jereweh, Indonesia. Data were analyzed through item–total correlation and Cronbach’s Alpha to determine validity and reliability, followed by IPA quadrant mapping and descriptive analysis for ESD indicators. All items achieved correlation values above 0.30, and the instrument demonstrated strong internal consistency with a Cronbach’s Alpha of 0.782. IPA results showed that Content Quality and Accessibility & Sustainability were classified in the Keep Up the Good Work quadrant, while Design & Navigation and Evaluation & Feedback fell into the Concentrate Here quadrant. ESD analysis indicated high ratings for digital literacy and collaboration, while sustainability values scored the lowest. These findings confirm that the instrument is valid and reliable and can effectively identify priority areas for improving Google Sites–based LMS within the principles of sustainable learning